ANALISIS PREFERENSI KONSUMEN PENGGUNA JASA MASKAPAI PENERBANGAN UNTUK RUTE SEMARANG-JAKARTA DENGAN METODE CHOICE-BASED CONJOINT (FULL PROFILE) - Vierga Dea Margaretha Sinaga; Diah Safitri; Agus Rusgiyono (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2015)
Airline services nowadays become one of the highly coveted options by many consumers for long-distance transportation. The increasing numbers of users makes airlines tightly compete each other to attract consumers’ interest. Thus, analysis to consumer preference has always been the starting point in market research as reference in creating new innovation. This research uses the choice-based conjoint analysis with the full profile as method of presentation. Conjoint analysis is a multivariate analysis method that can be used as a measurement for the level of preference. In the instrument, consumers were asked to choose one among three attribute combination of each choice set within 9 choice sets. Utility values were obtained by conditional logic model. The results show that for each attribute the order of preference is Price-Airport tax-Class-Facility. Judging from the value of its usefulness, the most preferred attribute by consumer is Airport tax and that Include is preferably from Exclude. For Price attribute, lower than 500 thousand rupiahs is the most preferred categories among others. In Class attribute, Business is more preferable than other categories. And for Facility attribute, entertainment is the most preferred one of other categories. Keywords: preferences, airlines, choice-based conjoint